Nuclear mechanosignaling in striated muscle diseases - Zhang, Bo; Powers, Joseph D.; McCulloch, Andrew D.; Chi, Neil C. (Frontiers in Physiology, 2023)
Mechanosignaling describes processes by which biomechanical stimuli are transduced into cellular responses. External biophysical forces can be transmitted via structural protein networks that span from the cellular membrane to the cytoskeleton and the nucleus, where they can regulate gene expression through a series of biomechanical and/or biochemical mechanosensitive mechanisms, including chromatin remodeling, translocation of transcriptional regulators, and epigenetic factors. Striated muscle cells, including cardiac and skeletal muscle myocytes, utilize these nuclear mechanosignaling mechanisms to respond to changes in their intracellular and extracellular mechanical environment and mediate gene expression and cell remodeling. In this brief review, we highlight and discuss recent experimental work focused on the pathway of biomechanical stimulus propagation at the nucleus-cytoskeleton interface of striated muscles, and the mechanisms by which these pathways regulate gene regulation, muscle structure, and function. We discuss nuclear and cytoskeletal protein mutations that affect mechanosignaling function in human and animal models of cardiomyopathy. Furthermore, current open questions and future challenges in investigating striated muscle nuclear mechanosignaling are further discussed.